2D molybdenum disulphide nanosheets incorporated with single heteroatoms for the electrochemical hydrogen evolution reaction. Issue 19 (7th May 2020) - Lau, Thomas H. M.; Foord, John S.; Tsang, S. C. Edman
Abstract : 2D nanosheets give enhanced surface area to volume ratios in particle morphology and they can also provide defined surface sites to disperse foreign atoms. Abstract : 2D nanosheets give enhanced surface area to volume ratios in particle morphology and they can also provide defined surface sites to disperse foreign atoms. Placing atoms of catalytic interest on 2D nanosheets as Single Atom Catalysts (SAC) represents one of the novel approaches due to their unique but tunable electronic and steric characteristics. Here in this mini-review, we particularly highlight some recent and important developments on heteroatom doped MoS2 nanosheets (SAC-MoS2 ) as catalysts for the electrochemical hydrogen evolution reaction (HER) from water, which could lead to opening up to a flagship of important renewable technologies in future. It is shown that the nature of dopants, doping positions and the polytypes of MoS2 nanosheets are the determining factors in the overall catalytic abilities of these functionalised nanosheets. This may serve to obtain atomic models which lead to further understanding of the 'metal–support interaction' in catalysis.